Exploring The Challenges Facing Teenage Mothers in School and How They Cope in the Wa West District - Adangabe, Amos Amuribadek; Emmanuella, Dogbey Alice; Tigtig, Julius (International Journal of Multidisciplinary: Applied Business and Education Research, 2021)
Education is a built-in mechanism that retains its essential value as a human right, not as a static commodity to be viewed in isolation from its larger context. Every person has the right to quality education and the ability to guarantee their human rights are secure for the long term. This research examined teenage mothers' struggles in school. The study employed a descriptive phenomenological approach. Twelve teenage mothers were selected, using a snowball sampling approach. Semi-structured interviews were used to collect data from these teenage mothers by audio taping. The data was transcribed, pursued and analysed thematically. The research revealed that teenage mothers in school face various difficulties in school, including lack of financial support, poor time management, low self-esteem, and emotional instability. The further revealed that majority of teenage mothers in school employ direct problem solving, cognitive decision-making, understanding, and constructive cognitive restructuring to cope with the challenges they face.